2014
DOI: 10.1152/ajpregu.00487.2013
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral vascular regulation and brain injury in preterm infants

Abstract: Cerebrovascular lesions, mainly germinal matrix hemorrhage and ischemic injury to the periventricular white matter, are major causes of adverse neurodevelopmental outcome in preterm infants. Cerebrovascular lesions and neuromorbidity increase with decreasing gestational age, with the white matter predominantly affected. Developmental immaturity in the cerebral circulation, including ongoing angiogenesis and vasoregulatory immaturity, plays a major role in the severity and pattern of preterm brain injury. Preve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 217 publications
(228 reference statements)
1
68
0
4
Order By: Relevance
“…This fixed AV-ratio is widely accepted in literature, although some studies suggest wide interindividual variation. 18,19 Assuming this fixed AV-ratio of 0.25 to calculate a reference value of tissue saturation from co-oximetry, we found that rStO 2;NIRS changed considerably less than expected: At low cerebral oxygenation, rStO 2;NIRS measured higher than rStO 2;COX , and at high oxygenation rStO 2;NIRS measurements were lower than rStO 2;COX . The NIRO-300 used in this study has previously been seen to react less to changes in oxygenation than the INVOS 5100 instrument (INVOS, Covidien, Boulder), which utilize the same spatially resolved NIRS technology and has a comparable source-detector separation, so it might to some extent be an issue of the specific NIRS instrument.…”
Section: Reactivity Of Cerebral Nirs Oximetry Assuming a Fixed Av-ratiomentioning
confidence: 70%
See 1 more Smart Citation
“…This fixed AV-ratio is widely accepted in literature, although some studies suggest wide interindividual variation. 18,19 Assuming this fixed AV-ratio of 0.25 to calculate a reference value of tissue saturation from co-oximetry, we found that rStO 2;NIRS changed considerably less than expected: At low cerebral oxygenation, rStO 2;NIRS measured higher than rStO 2;COX , and at high oxygenation rStO 2;NIRS measurements were lower than rStO 2;COX . The NIRO-300 used in this study has previously been seen to react less to changes in oxygenation than the INVOS 5100 instrument (INVOS, Covidien, Boulder), which utilize the same spatially resolved NIRS technology and has a comparable source-detector separation, so it might to some extent be an issue of the specific NIRS instrument.…”
Section: Reactivity Of Cerebral Nirs Oximetry Assuming a Fixed Av-ratiomentioning
confidence: 70%
“…We speculate that the reduced preload lowered the venous volumes of the upper limbs and the head, while cerebral arteries actively dilate as a response to the arterial hypotension due to the myogenic response. 10,18 Thus, arterial blood volume dominates the CBV at low MABP. This may explain the poor response of NIRS in terms of cerebral volume-weighted oxygenation when assuming a fixed AV-ratio, because NIRS increasingly reflects arterial blood, leading to higher results compared to fixed AV-ratio, as blood pressure is reduced.…”
Section: Reactivity Of Cerebral Nirs Oximetry Assuming a Fixed Av-ratiomentioning
confidence: 99%
“…The measurement of hPod is also based on spontaneous changes in Hb signals in a period less than 10 min and does not require the repetition of stimuli or an assumption regarding the hemodynamic response. Thus, hPod provides information regarding the dynamic properties of neurovascular function in addition to baseline values of physiological parameters accumulated through a large number of previous studies on CBF and metabolism in typically and atypically developing infants (15,56). hPod measured using fNIRS is a practical bedside tool, which can be used to assess the developmental status of the neurovascular system of the brain.…”
Section: Rapid Change Of Hpod From An In-phase To An Antiphase Pattermentioning
confidence: 99%
“…These findings suggest that circulatory development occurs with increasing CA and that neural development proceeds with increasing PMA (13,14). Although quantitative assessments of CBF and metabolism have been intensively studied in typically and atypically developing neonates and infants (15), the development of the dynamic properties of hemodynamics and metabolism remains to be uncovered.…”
mentioning
confidence: 99%
“…Accordingly, autoregulation results should be reviewed with changes in pH, PaCO 2 , PaO 2 , metabolism, blood glucose, sympathetic activation, and effects of neurovascular coupling [4,15,19,20] taken into account. We refer to other reviews for more in-depth information on these important confounders affecting cerebral vasoreactivity [4,7,[21][22][23].…”
Section: Concepts Of Static and Dynamic Autoregulationmentioning
confidence: 99%